Project portfolio selection method considering possibilities and influence of project stakeholders - Kononenko, Igor; Bukrieieva, Karina (My University, 2009)
A project portfolio selection method has been suggested, which is focused to systemic accounting for factors affecting the efficiency of a set of projects. In solving the task, the focus was on studying the impact of the human factor and the subjective component. The key point of the method is acquisition and assessment of information on the market, the organisation's strategy, the projects, the organisation's potential to implement the projects, and the influence of stakeholders. The set of projects selected for the portfolio is validated for admissibility in regard to the profit gained, income, financial feasibility, and the company's resource load. A model for optimising the project portfolio with algorithmic constraints has been suggested. The method can be applied for large and medium businesses.